Повышение контактной прочности зубчатых муфт путём модификации зубьев - Попов, А. П.; Кипреев, Ю. Н.; Савенков, О. И. (НТУ "ХПИ", 2011)
Впервые выполнено решение плоской задачи, которое распространяется на модели контакта цилиндра с клином, цилиндра с клином, имеющим в середине горизонтальный выступ, и цилиндра с площадкою, имитирующей условия взаимодействия зубьев. Получены зависимости для расчета максимальных напряжений и размеров участков контакта.

For the first time made the solution of the plane problem, which applies to models of contact of a cylinder with a wedge, a cylinder with a wedge having a horizontal lug in the middle, and a cylinder with the plane, imitating the conditions of interaction between the teeth has been carried out. The dependencies for the calculations of the maximum stresses and the contact area has been obtained.
Improving the gear couplings contact strength through teeth modification
Keywords: цилиндр; клин; напряжение; участок контакта; машиностроение